Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a)
\(\dfrac{4^2\cdot25^2+32\cdot125}{2^3\cdot5^2}\\ =\dfrac{\left(2^2\right)^2\cdot\left(5^2\right)^2+2^5\cdot5^3}{2^3\cdot5^2}\\ =\dfrac{2^{2\cdot2}\cdot5^{2\cdot2}+2^5\cdot5^3}{2^3\cdot5^2}\\ =\dfrac{2^4\cdot5^4+2^5\cdot5^3}{2^3\cdot5^2}\\ =\dfrac{2^4\cdot5^4}{2^3\cdot5^2}+\dfrac{2^5\cdot5^3}{2^3\cdot5^2}\\ =2\cdot5^2+2^2\cdot5\\ =2\cdot25+4\cdot5\\ =50+20\\ =70\)
c)
\(\dfrac{\left(1-\dfrac{4}{9}-2\right)\cdot16}{\left(2-3\right)^{-2}}+12\\ =\dfrac{\left(\dfrac{9}{9}-\dfrac{4}{9}-\dfrac{18}{9}\right)\cdot16}{\left(-1\right)^{-2}}+12\\ =\dfrac{\dfrac{-13}{9}\cdot16}{\dfrac{1}{\left(-1\right)^2}}+12\\ =\dfrac{\dfrac{-208}{9}}{1}+12\\ =\dfrac{-208}{9}+12\\ =\dfrac{-208}{9}+\dfrac{108}{9}\\ =\dfrac{100}{9}\)
Bài 2:
a)
\(\left(x+2\right)^2=36\\ \Rightarrow\left[{}\begin{matrix}x+2=6\\x+2=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=4\\x=-8\end{matrix}\right.\)
b)
\(\left(1,78^{2x-2}-1,78^x\right):1,78^x=0\\ \Leftrightarrow\dfrac{1,78^{2x-2}}{1,78^x}-\dfrac{1,78^x}{1,78^x}=0\\ \Leftrightarrow\dfrac{1,78^{2x-2}}{1,78^x}-1=0\\ \Leftrightarrow \dfrac{1,78^{2x-2}}{1,78^x}=1\\ \Leftrightarrow1,78^{2x-2}=1,78^x\\ \Leftrightarrow2x-2=x\\ \Leftrightarrow2x-x=2\\ \Leftrightarrow x=2\)
d) \(5^{\left(x-2\right)\left(x+3\right)}=1\)
\(\Rightarrow5^{\left(x-2\right)\left(x+3\right)}=5^0\)
\(\Leftrightarrow\left(x-2\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+3=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\)
Vậy \(x_1=-3;x_2=2\)
a) 27x : 3x = 9
(27 : 3)x = 9
9x = 91
x = 1
b) 25 : 5x =5
5x = 25 : 5
5x = 51
x = 1
c) 2 : (x + 2)2 = \(\dfrac{1}{18}\)
(x + 2)2 = 2 : \(\dfrac{1}{18}\)
(x + 2)2 = 36
\(\Rightarrow\left[{}\begin{matrix}x+2=6\\x+2=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=4\\x=-8\end{matrix}\right.\)
d) (5x - 1)2 = \(\dfrac{36}{49}\)
(5x - 1)2 = \(\left(\dfrac{6}{7}\right)^2\)
Bạn làm tiếp nha, mình có việc bận :v
a: \(\left(2x+1\right)^2=\left(x-1\right)^2\)
=>2x+1=x-1 hoặc 2x+1=1-x
=>x=-2 hoặc x=0
b: \(\left(x^2-5\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2-5=0\\x+3=0\end{matrix}\right.\Leftrightarrow x\in\left\{\sqrt{5};-\sqrt{5};-3\right\}\)
c: \(3\left(x-1\right)\left(2x-1\right)=5\left(x+8\right)\left(x-1\right)\)
\(\Leftrightarrow\left(x-1\right)\left(6x-3-5x-40\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-43\right)=0\)
hay \(x\in\left\{1;43\right\}\)
d: \(\Leftrightarrow x^2\left(x+1\right)+\left(x+1\right)=0\)
=>x+1=0
hay x=-1
1.a) \(\left(\frac{3}{5}\right)^{15}:\left(\frac{9}{25}\right)^5=\frac{3^{15}}{5^{15}}.\frac{5^{10}}{3^{10}}=\frac{3^5}{5^5}=\left(\frac{3}{5}\right)^5\)
b)\(\left(\frac{2}{3}\right)^{10}:\left(\frac{4}{9}\right)^4=\frac{2^{10}}{3^{10}}.\frac{3^8}{2^8}=\frac{2^2}{3^2}=\left(\frac{2}{3}\right)^2\)
2.
a)\(2^x=4\Rightarrow2^x=2^2\Rightarrow x=2\)
b)\(x^3=-27\Rightarrow x^3=-3^3\Rightarrow x=-3\)
c)\(x^2=16\Rightarrow x=\pm4\)
d)\(\left(x+1\right)^2=9\Rightarrow\hept{\begin{cases}x+1=3\Rightarrow x=2\\x+1=-3\Rightarrow x=-4\end{cases}}\)
a)(1/3)4-x=(1/4)3
1/81 -x =1/64
x= 1/81-1/64
x=-17/5184
b)(1/5) . x =(1/5)8 : (1/5)3
(1/5) . x =(1/5)5
x=(1/5)5 : (1/5)
x=(1/5)4
x=1/625
c)(2.x -3 )2=25
=> 2.x-3=5 hoặc =-5
nếu 2.x-3=5 nếu 2.x-3=-5
2.x=5+3 2.x=-5+3
2.x=8 2.x=-2
x=8/2=4 x=-2/2=-1
d)(3x+2)5=-243
(3x+2)5 =(-3)5
=>3x+2=-3
3x=-3+2
3x=-1
x=-1/3
c)(2x-3)\(^2\)=\(5^2\) hoặc(2x-3)\(^2\)=(-5)\(^2\) (2x-3)\(=5\) hoặc (2x-3)=(-5) 2x=8 hoặc 2x=-2 x=4 hoặc x=-1
\(\left(\dfrac{1}{5}\right)^{25}\cdot\left(\dfrac{1}{5}\right)^{30}\)
\(=\left(\dfrac{1}{5}\right)^{25+30}\)
\(=\left(\dfrac{1}{5}\right)^{55}\)
\(\left(\dfrac{1}{16}\right)^3:\left(\dfrac{1}{8}\right)^2\)
\(=\left[\left(\dfrac{1}{2}\right)^4\right]^3:\left[\left(\dfrac{1}{2}\right)^3\right]^2\)
\(=\left(\dfrac{1}{2}\right)^{12}:\left(\dfrac{1}{2}\right)^6\)
\(=\left(\dfrac{1}{2}\right)^{12-6}=\left(\dfrac{1}{2}\right)^6\)
\(\left(x^3\right)^2:\left(x^2\right)^3\)
\(=x^{3\cdot2-2\cdot3}\)
\(=x^0=1\)